Jenis Pekerjaan dan Karir di Bidang Otomotif bagi Lulusan Jurusan Teknik Otomotif - Sugiarto, Toto; Giatman, M.; Syah, Nurhasan; Putra, Dwi Sudarno; Hidayat, Nuzul; Baharudin, Agus (Universitas Negeri Padang, 2024)
The research aims to describe the types of jobs in the automotive sector and record jobs entered by automotive departement engineering graduates. Research is a type of qualitative descriptive, the data used is in the form of qualitative data from interviews, field observations, document analysis, and survey results. The research sample was 93 respondents, 69 respondents used a questionnaire, and 24 respondents spread over 13 companies were conducted using interview and observation techniques. The results of the study show that there are several types of jobs that graduates can enter and pursue as well as careers, into four career fields, namely: technician, sales marketing, training instructor, and teacher. For a career in mechanics, the career paths are: mechanic, mechanic team leader, mechanic chief, service advisor, workshop head, and service manager. Career paths in sales marketing, namely: sales during training, sales marketing 1 (s1), sales marketing 2 (s2), sales marketing 3 (s3), sales supervisor, marketing manager , and branch head. Career paths in the field of instructor training, namely: training instructor, head instructor, instructor manager, head of the HRD division, and HRD manager. Career paths as a teacher, namely: teachers, heads of workshop, heads of departments, vice principals, school principals, school supervisors, and heads of the education sector. In addition to the four fields of work and career paths, there are several other types of work, such as: heavy equipment operator, aircraft maintenance, few are self employed in the automotive sector (car repair, car buying and selling, car rental business).